The Impact of Brainstorming Techniques and Story Development on the Effectiveness of Digital Marketing Campaigns: An Empirical Study in the Digital Era - Hidayat, Ade Suzan Afianty; Riskamelisyah; Lenggana, Wulan Furrie (Dinasti Publisher, 2025)
This study examines the impact of brainstorming techniques and story development in digital marketing campaigns on engagement, conversion rates, and brand awareness. The use of brainstorming techniques that involve collaboration among marketing teams generates more creative, relevant, and engaging campaign ideas for the audience, which increases interactions such as likes, shares, and comments, as well as encourages further actions like purchases. Meanwhile, structured and emotional story development can create a deeper connection between the brand and the audience, ultimately enhancing brand awareness in the market. This study shows that both techniques can significantly improve the effectiveness of digital marketing campaigns, in terms of boosting audience engagement, conversion rates, and brand recognition. The practical implications of this research suggest that companies should involve the entire team in brainstorming sessions to create fresher and more relevant campaign ideas. Moreover, emotional storytelling development should be an integral part of marketing strategies. This research also opens up opportunities to compare brainstorming techniques with other creative methods and explore their application across various industry sectors. The findings of this study can enrich content marketing and storytelling theories, and serve as a guide for companies in designing more effective and creative digital marketing campaigns